Democratization and Violent Conflict: Is There A Scandinavian Exception?. (9th July 2020) - Andersen, David
Abstract : The notion that the paths to democracy in Scandinavia were exceptionally peaceful remains a popular argument, but an equally large number of studies opposes this view. This research note provides the first systematic attempt to compare records of violence during democratization in Scandinavia with other regions and countries. By using Varieties of Democracy data, I construct novel measures of democratization and violent conflict that align with extant propositions on Scandinavian exceptionalism and conflict‐democratization research while appreciating multiple dimensions of democratization for a global sample of countries from 1789 to 2018. The results show stable support for a substantial Scandinavian exception of peaceful democratization, but only evidently so for moves toward greater executive constraints and civil and political liberties. The exception is less clear for democratization considering competitive elections and suffrage. On this basis, I propose that we may improve the understanding of the causes of Scandinavian democratic exceptionalism and democratic sustainability more generally by studying the origins of peaceful democratization in Scandinavia compared with Western Europe in the 'age of liberalization' from approx. the mid‐eighteenth to the mid‐nineteenth century.